1995
DOI: 10.1177/088840649501800202
|View full text |Cite
|
Sign up to set email alerts
|

Managing Change in a Research University Special Education Program

Abstract: In the following case study, we describe the discourse and external events preceding a change in the culture of the University of Washington Special Education program. Activities that followed were typical of a paradigm shift as described in the literature. The study concludes with evidence of intense collaborative activity followed by significant programmatic and curricular modification. We end with a vision of future program directions and descriptions of the type of personnel needed to implement our vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Other programs attended to integration across courses by teaching courses in integrated blocks, using weekly seminars, or both. Furthermore, many programs used case-based approaches, portfolios, and weekly seminars to help students reflect on their learning across courses and practicum experiences (Affleck & Lowenbraun, 1995;Bay & Lopez-Reyna, 1997;Burstein & Sears, 1998;Emond, 1995;Epanchin & Wooley-Brown, 1993;Lovingfoss et al, 2001;May et al, 1989;Otis-Wilborn & Winn, 2000;Sobel, French, & Filbin, 1998).…”
Section: Crafting Extensive Field Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Other programs attended to integration across courses by teaching courses in integrated blocks, using weekly seminars, or both. Furthermore, many programs used case-based approaches, portfolios, and weekly seminars to help students reflect on their learning across courses and practicum experiences (Affleck & Lowenbraun, 1995;Bay & Lopez-Reyna, 1997;Burstein & Sears, 1998;Emond, 1995;Epanchin & Wooley-Brown, 1993;Lovingfoss et al, 2001;May et al, 1989;Otis-Wilborn & Winn, 2000;Sobel, French, & Filbin, 1998).…”
Section: Crafting Extensive Field Experiencesmentioning
confidence: 99%
“…Thirty-five (55%) of the descriptions suggested that program faculty viewed learning to teach from a different epistemological stance (Affleck & Lowenbraun, 1995;Anderson & Baker, 1999;Epanchin & Wooley-Brown, 1993;Hall et al, 1997). These teacher educators viewed teacher learning as the collective examination of multiple knowledge bases, including, but not limited to, knowledge generated by experts.…”
Section: Maintaining a Positivist Or Constructivist Orientation Toward Teacher Knowledgementioning
confidence: 99%
See 2 more Smart Citations